2022
DOI: 10.33588/rn.7507.2022123
|View full text |Cite
|
Sign up to set email alerts
|

El papel de los cannabinoides en los trastornos del neurodesarrollo de niños y adolescentes

Abstract: Introducción. Los trastornos del neurodesarrollo tienen una etiología multifactorial que resulta de la interacción entre factores biológicos y ambientales. La base biológica de muchos de estos trastornos se comprende sólo parcialmente, lo que hace que las intervenciones terapéuticas, especialmente las farmacológicas, sean particularmente difíciles. El impacto del cannabis medicinal en los trastornos neurológicos y psiquiátricos se ha estudiado durante mucho tiempo. Este estudio tuvo como objetivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The majority (70%) of children and adolescents with autism spectrum disorder display aggressive behavior, and more than 25% of them also display self-injurious behavior. The standard treatment in Europe is either aripiprazole or risperidone, but their use, either alone or in combination, does not always have optimal efficacy [ 208 ].…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (70%) of children and adolescents with autism spectrum disorder display aggressive behavior, and more than 25% of them also display self-injurious behavior. The standard treatment in Europe is either aripiprazole or risperidone, but their use, either alone or in combination, does not always have optimal efficacy [ 208 ].…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
“…After one month, 4.2% of patients discontinued treatment, and after six months, this percentage increased to 8.3%. The results showed that 25.2% of patients reported at least one side effect: anxiety (6.6%), drowsiness (3.2%), psychoactive symptoms (3.2%), increased appetite (3.2%), digestive disturbances (3.2%), dry mouth (2.2%) and lack of appetite (2.2%) [ 208 ]. CBD shows significant potential to safely alleviate many of the symptoms affecting children and adolescents on the autism spectrum.…”
Section: Neurological Disorders and Cannabis Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…O canabidiol possui um limite de toxicidade relativamente alto e pode ter propriedades ansiolíticas, antipsicóticas e neuroprotetoras. Evidências clínicas sugerem que o tratamento precoce com canabidiol pode ser uma terapia promissora para transtornos do neurodesenvolvimento, incluindo deficiência intelectual, transtornos do espectro autista, tiques e transtorno de déficit de atenção/hiperatividade (Freitas, 2022).…”
Section: Tdahunclassified